Sertoli Cell Immune Regulation: A Double-Edged Sword - Washburn, Rachel L.; Hibler, Taylor; Kaur, Gurvinder; Dufour, Jannette M. (Frontiers in Immunology, 2022)
The testis must create and maintain an immune privileged environment to protect maturing germ cells from autoimmune destruction. The establishment of this protective environment is due, at least in part, to Sertoli cells. Sertoli cells line the seminiferous tubules and form the blood-testis barrier (BTB), a barrier between advanced germ cells and the immune system. The BTB compartmentalizes the germ cells and facilitates the appropriate microenvironment necessary for spermatogenesis. Further, Sertoli cells modulate innate and adaptive immune processes through production of immunoregulatory compounds. Sertoli cells, when transplanted ectopically (outside the testis), can also protect transplanted tissue from the recipient’s immune system and reduce immune complications in autoimmune diseases primarily by immune regulation. These properties make Sertoli cells an attractive candidate for inflammatory disease treatments and cell-based therapies. Conversely, the same properties that protect the germ cells also allow the testis to act as a reservoir site for infections. Interestingly, Sertoli cells also have the ability to mount an antimicrobial response, if necessary, as in the case of infections. This review aims to explore how Sertoli cells act as a double-edged sword to both protect germ cells from an autoimmune response and activate innate and adaptive immune responses to fight off infections.